Pastoral Counseling Care for People with Depression Impacts Self-harm and Suicidal Ideation - Taroreh, Christina Cynthia; Brek, Yohan; Wagiu, Meily Meiny; Luma, Subaedah (JURNAL TERUNA BHAKTI, 2024)
People with depression have potential and symptoms that lead to acts of self-harm and a desire to end life. Conventional approaches in this regard, medical and psychological approaches, can overcome depression but have limitations, so there is a crucial need to expand interventions, including in spiritual contexts. People with depression must be helped holistically so that Pastoral Counseling Assistance can be the answer. This paper aims to describe pastoral counseling assistance as an indispensable effort for sufferers (victims) of depression impacting self-harm and suicide to get complete and sustainable recovery by restoring themselves, reasoning, and having hope and enthusiasm to live the reality of life. This research uses qualitative methods with a literature-review approach to obtaining relevant data. The results of this study show that holistic pastoral counseling assistance and using an integrated approach based on conditions and needs is effective in helping people with depression overcome depression and negative impulses.